"If a War It May Be Called": The Peace Policy with American Indians. Issue 1 (18th June 2014) - Graber, Jennifer
Abstract: In 1869, President Ulysses S. Grant initiated the "Peace Policy" with American Indians, an approach that privileged humane interactions with native peoples and allowed religious groups to run reservations across the American West. The Society of Friends, or Quakers, administered the largest number of reservations and symbolized the policy's benevolent aims. This essay explores varying Quaker understandings of peaceful relations with Indians as well as the general public's perception of the Friends' nonviolence. The essay focuses on an 1871 Indian attack on an overland wagon train, including Quaker engagements with the army in the attack's aftermath. Despite the Society's part in an emerging culture of threat against Plains Indians, Americans continued to consider both the Society and the policy to be peaceful. As such, this episode proves useful for understanding the intersections of religion and violence in United States history. Close analysis of the internal Quaker debate about military engagement, as well as Americans' ongoing identification of the policy with nonviolence, shows how religious groups and religious language were employed to reclassify episodes of violence as peace.